Impulsivity and sexual addiction: factor structure and criterion-related validity of the sexual addiction screening test in Mexican adults - Mejía Cruz, Diana; Avila Chauvet, Laurent; Villalobos-Gallegos, Luis; Toledo-Lozano, Christian Gabriel (Frontiers in Psychiatry, 2023)
Sexual addiction is associated with serious health problems. Due to that fact, it is quite important to perform a comprehensive assessment. The Sex Addiction Screening Test (SAST-R) is a self-administered questionnaire with good psychometric properties used in several countries. Our study conducts a cross-cultural adaptation of the SAST-R on the Mexican population. The original version of the SAST-R was translated into Mexican Spanish, and we performed a pilot with 23 participants to be sure that the participants understood the meaning of the items. The final version was administered to 370 adults who completed the SAST-R, and measures of impulsivity (the Kirby questionnaire), reward/punishment responsivity (BIS-BAS scale), personality (BIG-Five), and psychological distress (SCL-90). The confirmatory factor analysis (CFA) with a five-factor model with one second-order factor model had the best fit. Reliability analysis suggests acceptable internal consistency (α = 0.80). The SAST-R scores exhibited significant correlations with several variables. Specifically, they showed a positive correlation with the neuroticism scale (r = 0.11, p < 0.05), a negative correlation with the conscientiousness scale (r = –0.21, p < 0.01), a negative correlation with the BIS scale (r = −0.11, p < 0.05), and a positive correlation with psychological distress (r = 0.34, p < 0.01). Notably, there were no significant correlations observed with variables that we initially expected to have a substantial association, such as impulsivity (r = –0.004, p > 0.05) and the three BAS subscales (p > 0.05). We found with an algorithm that psychological distress, impulsivity, neuroticism, and agreeableness were the good predictors to identify high scores of hypersexuality. Our results confirmed that the Mexican Spanish version of the SAST-R has good psychometric properties to be used in future research.